Subclinical synovitis detected by magnetic resonance imaging and ultrasonography following clinical remission in patients with rheumatoid arthritis: A retrospective study. Issue 1 (4th October 2021) - Nawata, Masao; Someya, Kazuki; Aritomi, Takafumi; Funada, Masashi; Nakamura, Katsumi; Saito, Kazuyoshi; Tanaka, Yoshiya
Abstract: Background: Subjective residual symptoms persist after clinical remission of rheumatoid arthritis (RA) in Japanese patients. Few studies have examined the relationship between these symptoms and subclinical inflammation using high‐sensitivity imaging (musculoskeletal ultrasound [MSUS] and magnetic resonance imaging [MRI]). We examined the relationship between subjective residual symptoms and imaging findings in patients with RA who achieved clinical remission. Methods: We enrolled 30 patients with RA. The primary endpoint was the patients' subjective residual symptoms. The secondary endpoint was the relationship between the aforementioned symptoms and imaging findings. Results: Despite a mean Simplified Disease Activity Index of 1.3, imaging evaluation revealed inflammatory findings. In the multivariate analysis, the Health Assessment Questionnaire Disability Index (HAQ‐DI) and pain visual analog scale (VAS) scores were extracted as independent related factors of subjective residual symptoms. The stratified analysis according to HAQ‐DI showed a significant difference in synovitis on MRI between patients with and without residual disability (12.0 ± 8.7 vs. 5.3 ± 5.3, respectively; p = 0.0192). However, MSUS scores showed no significant difference in these two groups. In addition, no significant differences were found in MSUS and MRI scores between patients with and without residual pain VAS. Conclusions: Our findings demonstrated residual synovitis related to patient‐reported outcomes in patients with RA who achieved clinical remission. In particular, patients with an HAQ‐DI score of >0.25 even after achieving clinical remission should be further examined by MRI and/or MSUS for the evaluation of residual synovitis. Key points: Significant findings of the study: This study evaluated subjective residual symptoms and imaging findings using musculoskeletal ultrasound and magnetic resonance imaging in patients with rheumatoid arthritis (RA) who achieved clinical remission. What this study adds: A Health Assessment Questionnaire Disability Index score of ≤0.25 may indicate reduced severity of residual synovitis in patients with RA following clinical remission. Abstract : Subclinical synovitis detected by MRI and US following clinical remission in patients with rheumatoid arthritis